Prognostic value of baseline versus 6-month follow infarct size in patients with reperfused STEMI. (14th October 2021) - Valente, F; Gavara, J; Calvo, M; Rello, P; Maymi, M; Barrabes, J; Sao-Aviles, A; Burcet, G; Cuellar, H; Otaegui, I; Garcia-Blanco, B; Ferreira, I; et al.
Abstract: Background: Acute infarct size is a predictor of clinical outcomes in acute ST segment elevation myocardial infarction (STEMI) patients, although its prognostic value has differed between studies. In acute STEMI, infarct size is often overestimated due to the presence of extensive myocardial oedema, a confounder that is no longer present at a 6-month follow-up study. It was our purpose to assess whether infarct size in the acute phase or at 6-months follow-up provided superior prognostic information in STEMI patients. Methods: STEMI patients who underwent successful primary percutaneous revascularization were included and a cardiac magnetic resonance (CMR) was performed between 5–7 days after STEMI and at 6 months to study infarct size (as a % of myocardial mass). The primary endpoint was a composite of cardiovascular mortality, hospitalization for heart failure and ventricular arrhythmia. Results: A total of 796 patients were included (mean age 58.3±11.5 years, 82.4% male, 52.3% anterior infarction). During a mean follow-up of 59 months, 59 patients (7.4%) presented with the primary end-point (cardiovascular death n=7, hospitalization for heart failure n=52, ventricular arrhythmia n=1). ROC curve analysis (figure 1) showed a non-significant difference between baseline and 6-month infarct size for the prediction of the primary endpoint (baseline AUC 0.685 95% CI 0.610–0.760, 6-month AUC 0.713 95% CI 0.643–0.782, p=0.60). Optimal cut-off values for baseline and 6-months follow-up infarct size for prediction of outcomes, respectively 22% and 17.5%, were used for Kaplan-Meier curve analysis (figure 2). Conclusion: Infarct size estimated during the first week after STEMI and at 6-months follow-up showed similar predictive value and with similar cut-off values. Therefore, the prognostic information provided by infarct size can be obtained during initial STEMI admission and does not require a waiting period for infarct size stabilization. Funding Acknowledgement: Type of funding sources: None.